PERTUMBUHAN DAN HASIL DUA VARIETAS CABAI RAWIT (Capsicum frutescens L.) DITANAM DI LUAR MUSIM DENGAN PERLAKUAN PUPUK DAUN - Armiati, Merita Eka; Jaya, I Komang Damar; Windarningsih, Mery (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
Cayenne pepper (Capsicum frutescens L.) is one of the horticultural commodities that needed throughout the year. In certain season, such as the rainy season, production tends to be low due to the low yield of chilies. Therefore, it is important to get the cultivation technology of cayenne pepper outside the season. This research aimed to study growth and yield of two varieties of cayenne pepper grown off-season treated with different concentrations of POMI foliar fertilizer. One experiment was carried out in October 2020 to March 2021 in a dryland of Gumantar Village, Kayangan District, North Lombok Regency. The factors tested were varieties (Sret and Taruna) and POMI foliar fertilizer concentrations (0%, 1.0% and 1.5%). The treatments were arranged using a factorial randomized block design (RBD) with three replications. The results showed that the variety and concentration of POMI leaf fertilizer interacted in affecting the number of flowers and the number of fruits. The highest number of flowers and fruit was produced by Taruna variety which was treated with POMI foliar fertilizer at 1.5% concentration. Taruna variety showed a better growth and yield than Sret while the concentration of POMI foliar fertilizer which produced the best growth and yield was 1.5%. To get high yields in off-season chili cultivation, it is recommended to grow Taruna varieties and be treated with POMI foliar fertilizer with a concentration of 1.5%.